Assessing the state of the rice milling sector in Nigeria: The role of policy for growth and modernization - Johnson, Michael E.; Masias, Ian (International Food Policy Research Institute, 2017)
We use an industry profit maximization model to conduct an ex-post impact assessment on the extent the rice milling sector in Nigeria has grown and improved its performance in producing high quality premium rice following major public sector interventions made under the Agricultural Transformation Agenda. Given challenges with the availability and qual-ity of data, this assessment looks at the changes between two periods, 2009 and 2013, and simulates the performance of the sector under different technology capacities and policy scenarios. We find that the government has been success-ful in expanding quality paddy production and milling capacity in the country along with an increase in capacity utilization in the medium and large-scale milling sub-sectors. As a result, the production of premium quality rice has increased by approximately 0.5 million metric tons between the two periods. Despite these gains, the industry did not see any overall increase in employment in the medium and large-scale sub-sectors. Further focus by the government on expanding the supply of high quality rice paddy, while maintaining high tariffs to keep the medium and large scale milling sector viable, may provide the best opportunity for Nigeria to reach its goal of self-sufficiency in rice production.